(untitled) (Research, Society and Development, 2021)
To analyze eating patterns and behaviors in children with Autistic Spectrum Disorder (ASD).This is an integrative literature review. The search for articles was performed in the databases of the VHL, Scielo, Lilacs, PubMED and Academic Google between the periods of August 2020 to June 2021. 62 articles were found and only 11 were selected for discussion of the results. The descriptors used were: “Eating Patterns”, “Eating Behavior”, and “Autistic Spectrum Disorder”. The inclusion criteria were original articles, indexed in the selected databases, in the languages: Portuguese and English; published between 2011 and 2021. Exclusion criteria were publications of theses, conference proceedings, dissertations, monographs and articles that did not adhere to the theme. Regarding dietary patterns, children prefer foods with high energy density such as sugary drinks and crunchy foods, and have a low consumption of fruits, vegetables, fish and dairy products. As for the behaviors, a great food refusal and reluctance to eat new foods such as fruits, vegetables, fish and dairy products were identified, in addition to problematic behaviors such as resistance to sit at the table and eat with other people, enter the cafeteria and not sit at the table until the meal is over, and in accepting new preparations, it was also evident that the behavior of parents directly influences food selectivity and their choices. The monitoring of parents of children with ASD will bring positive results in the understanding of these children’s eating patterns and behaviors, to contribute to professionals in the area.